Impact of total ischemic time (TIT) on 1-month clinical outcomes at a tertiary cardiology centre (TCC) with a limited primary percutaneous coronary intervention (LPPCI) service in the management of ST-elevation myocardial infarction (STEMI) - Khor, H. K.; NADIA, M. N.; LIEW, Y. X.; Koh, S. S.; Fong, A.Y.Y.; Chung, B.K.; Ling, H.S.; Chow, Han Bing; Chan, En Ze; Thien, L.K.; Pang, I. X.; Shu, F.E.P.; et al. (Elsevier, 2023)
PPCI is the recommended treatment strategy over fibrinolytic for treatment of STEMI. However, majority of hospitals offer only a LPPCI service or fibrinolytic strategy for STEMI. TIT is associated with clinical outcomes for both treatment strategies. At a single public access tertiary cardiology centre (SPATCC) covering a large geographical area, a LPPCI service is provided.